Akuntansi Keperilakuan dalam Pitutur Luhur Kejawen - Nia, Anggun Vika Taman; Bullah, Habi (Juara: Jurnal Riset Akuntansi, 2024)
Accounting practices are closely related to unethical actions/behavior that can harm the parties concerned. Which behavior can be shaped by its environment, one of which is culture. This study aims to determine how pitutur luhur kejawen teaches behavioral accounting values so that they can be used as guidelines and instructions. This research uses an interpretative qualitative approach with metaphor as a review tool. Primary data and secondary data are the types of data used. Data collection techniques were conducted by means of interviews, literature and documentation. The results showed that pitutur luhur kejawen is very relevant to be used as a foundation for accountants. The values contained in pitutur luhur kejawen can influence intention, individual behavior control.